Comparative Analysis of Apache 2 Performance in Docker Containers vs Native Environment - Rizky Bintang Saputra; Subektiningsih Subektiningsih (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2023)
Web servers have become crucial to facilitate access to and distribute such content on the internet. In this case, Docker containerization technology offers a solution. Docker allows developers to package applications and dependencies in one container, making deploying web servers faster and easier. But with these features, is there any performance that must be sacrificed if we choose to use docker in our web server deployment process. We will look at how much performance will be sacrificed. However, we must thoroughly analyze how Apache2 performs when running in a Docker container compared to running natively. That's why we're conducting a study to compare the performance of Apache2 in a Docker container versus a native environment using experimental methods. For this study, we'll use the Apache bench tool to test Apache2's performance in both environments. By experimenting, it should become clear how the performance of Docker containers compares to native environments when developing web servers. The research shows that Apache2 performance on native hosts is about 5-10% better than in a docker environment in handling small request loads. The better performance here refers to the parameters we tested: total time results, requests per second, and transfer speed. The request load variation can differ depending on the server specification itself. Although Docker offers features in terms of application isolation and scalability, our results show that running Apache2 natively is more efficient without changing its default configuration. The additional overhead Docker can be required to run the docker system in isolating the application; in this case, the virtualization layer is required to run Apache2 inside a Docker container. This can affect application performance and cause a slight performance degradation compared to using the host operating system directly. This research aims to inform developers about the performance difference between apache2 in Docker and the native environment. It will help them make informed decisions about deployment environments. Docker offers appealing features, but its performance may need to improve.  Test results show that the native host performs better, although its feature set is not as extensive as that of Docker.